Test of the classic model for predicting endurance running performance - McLaughlin, J. E.; Howley, E. T.; Bassett, D. R.; Thompson, D. L.; Fitzhugh, E. C. (Medicine & Science in Sports & Exercise, 2010)
Purpose: To compare the classic physiological variables linked to endurance performance (VO2max, %VO2max at lactate threshold (LT), and running economy (RE)) with peak treadmill velocity (PTV) as predictors of performance in a 16-km time trial.